'O Hidden Face!' : an analysis and contextualisation of Priaulx Rainier's 'Requiem' - Van Rhyn, Chris (Stellenbosch : Stellenbosch University, 2010)
Thesis (MMUS (Music))--Stellenbosch University, 2010.